Воспитательный процесс и общественная работа в школах города Костаная (вторая половина ХХ века) - Айтмухамбетов, А.А.; Молдабаева, С.А. (My University, 2016)
In this article an educator process and social work of schools of city of Kostanay are lighted up in a historical aspect. Principles of educator work, that corresponded to soviet ideology, open up.
Keywords: ducator work; principles of educator work; soviet ideology; organization of cultural and mass work